Anglo-American antiphony : the late romanticism of Tennyson and Emerson - Brantley, Richard E. (University Press of Florida, 1994)
This is Richard Brantley's most wide-ranging and his most personal book. It connects the epistemology of John Locke to evangelical Christianity, showing how the late ("but not belated") Romanticism of Emerson's prose and Tennyson's In Memoriam A.H.H. exemplifies the period's trust in experience as the best means of knowing what is true. Interpreting their work in light of the eighteenth-century thought of John Wesley (founder of British Methodism) and Jonathan Edwards (leader of the American Great Awakening), Brantley composes a complex harmony of ideas, much as the antiphonal voices in a divided chancel choir rejoice in agreeable, yet complicated, song. With a willingness to risk the widest ramifications of his ideas, Brantley explores the creative tension between empiricism and evangelicalism, reaffirming the hopefulness of Romantic literature and of the Romantic writers who used their poetry and prose to examine issues of personal urgency. He seeks specific answers to the question of ultimate meaning in human existence, boldly asserting that the optimism of Tennyson and Emerson "makes so much sense for their social world that it may even make sense for today's individual-in-society." His method is relatively unsystematic, for he invokes Keats's "Negative Capability," the ability to rest with "uncertainties, Mysteries, doubts, without any irritable reaching after fact and reason." While emphasizing this value amid multiple perspectives and cultures, Brantley, in this concluding volume of his historical-critical tetralogy, aspires to the condition of open mind and warm heart that he finds in Wesley, Edwards, Tennyson, and Emerson